ANALISIS INTEGRASI PASAR DAN TRANSMISI HARGA CABAI MERAH BESAR DI KOTA MATARAM (KASUS: PASAR MANDALIKA DAN PASAR KEBON ROEK) - Aprilianti, Aprilianti; Sahidu, Arifuddin; Miharja, Dian Lestari (JURNAL AGRIMANSION, 2023)
This study aims to determine the price transmission that occurs in the main market (Mandalika market) to the retail market (Kebon Roek market) and to determine the level of market integration that occurs between the main market (Mandalika market) and the retail market (Kebon Roek market). The method used namely descriptive method. The unit of analysis in this study was the price of large red chilies in the city of Mataram, with two comparative markets, namely the Mandalika main market and the Kebon roek retail market. The type of data used is quantitative data. The data source used is secondary data. The data analysis used is ET and IMC analysis. The results of this study indicate that: (1) The price transmission that occurs between the Mandalika main market and the Kebon Roek retail market is running inefficiently. This can be seen from the ET value < 1, which is 0. 734, indicating that if there is a change in the price of large red chilies at the wholesale market level by 1%, the price at the retail market level will change by 734%. It can be stated that price changes at the retail market level are not well transmitted to prices at the main market level. This shows that there is an imperfect competition market in the marketing of large red chilies in both markets. (2) Market integration in the marketing of Large Red Chili at the Mandalika Main Market with the Kebon Roek Retail Market in Mataram City, namely IMC = 1. 710 means that IMC > 1 means that market integration is low. This shows that the prices at the Mandalika Main Market are not fully transformed to the market level Kebon Roek retailer.